Obedience pressure and group pressure: An experimental study on whistleblowing - Ulfa, Ulfa; Utami, Intiyas (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
Obedience pressure is when individuals receive commands from their superiors to act unethically. Group pressure refers to individuals within a group that considers unethical actions acceptable. Meanwhile, whistleblowing refers to the reporting action of whistleblowers aware of fraud in their workplaces. This research aims to examine the causal association between obedience pressure and group pressure, and whistleblowing intentions. This research uses a 2x2 between-subject experimental study. Our subjects are students from an accounting department in Central Java. Our results demonstrate that individuals under low obedience pressure have higher whistleblowing intentions than those under high. Second, individuals under low group pressure have higher whistleblowing intentions than individuals under high group pressure. Third, there is an interaction between obedience pressure and group pressure on whistleblowing intentions. This research contributes to the whistleblowing literature and informs companies in developing an optimal whistleblowing system.